2007
DOI: 10.1097/01.aog.0000255973.92450.24
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Urinary Incontinence Among Healthy, Older Women

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 16 publications
3
63
0
8
Order By: Relevance
“…Some strategies can minimize the effects of UI during the aging process. Physical activity acts positively on the continence mechanism because it helps maintain body weight and prevent obesity, since fat can cause chronic elevation of intraabdominal pressure and weaken pelvic support structures 7,8 . Ree, Nygaard and Bø 9 observed that strength training can increase the volume of the pelvic floor muscles, enabling contraction at certain times when there is increased intra-abdominal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Some strategies can minimize the effects of UI during the aging process. Physical activity acts positively on the continence mechanism because it helps maintain body weight and prevent obesity, since fat can cause chronic elevation of intraabdominal pressure and weaken pelvic support structures 7,8 . Ree, Nygaard and Bø 9 observed that strength training can increase the volume of the pelvic floor muscles, enabling contraction at certain times when there is increased intra-abdominal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Once incontinence is present, decreased physical activity may further exacerbate it, as lack of physical activity and greater weight may also lead to increased stress incontinence. 6,7 In addition, although the prevalence of stress incontinence increases with age, 8 it is not uncommon in women of reproductive age. The rate of stress incontinence in women aged 30-39 years was approximately 10% in one survey.…”
Section: Introduction Gmentioning
confidence: 99%
“…Para esses autores, a menor incidência pode ser atribuída aos benefícios da atividade física no mecanismo de continência 29,30 .…”
Section: Discussionunclassified